Analisis Kelayakan Usahatani Padi Organik di Desa Bareng Kecamatan Bareng Kabupaten Jombang - Latif, Abdul; Nasirudin, Mohamad; Qomariyah, Siti Nur (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2021)
This study aims to (1) find out the amount of organic rice farming income in Bareng Village, Bareng subdistrict, Jombang District (2) to find out the feasibility level of organic rice farming in the review of the R/C Ratio in Bareng Village, Bareng subdistrict, Jombang District. The method used is the method (cross-section). The total sample of 7 farmers. The results of the analysis showed that (1) the production in two planting cycle processes in organic rice farming amounted to Rp 23,269,738, consisting of a fixed cost of Rp 8,427,594 and a variable cost of 14,842,143 (2) The Total revenue to Rp 31,971,428 and total income in two planting cycles in organic rice farming Rp 8,701,690 Total R /C in organic rice farming per two planting cycles in farmer groups in Bareng Village, Bareng subdistrict, Jombang District. Means the cost of production of Rp. 1 can generate an income of Rp 1,374 so that organic rice farming in Bareng village is profitable and worth trying.